Crop Intensification Project Activities and Livelihood Improvement in Rwanda: A Case of Maize Farmers in Munyaga Sector, Rwamagana District - Sezirahiga, Jean Bosco; Mukamazimpaka, Marie Claire (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2021)
Fruit main objective of this research is to examine the impact of Crop Intensification Program activities on the improvement of livelihoods in Rwanda. Concerning the sampling technique, the methodology to be used in information collection was questionnaire and interview guide that was conducted together with observation which was helpful in interpreting results. This research was conducted at the maize farmers in four cells located in Munyaga sector totaling 99 households making up the sample of respondents which was chosen randomly from the total of 6978 maize farmers. The findings proves that there is a relationship between increased land cultivation and increased diet and food security (p=.479 with sig=.000) between increased land cultivation and improved health (p=.730 of sig=.000) between increased seeds, yield and improved household income (p=.936 with sig=.000) between improved household income and improved health (p=.630 of sig=.000) between increased diet and food security and improved health (p=.688 with sig=.000) because all calculated p- values are less than the 0.01 level of significance. Therefore, this implies that there is a relationship between predictors of crop intensification project activities and livelihood improvement of maize farmers in Munyaga Sector of Rwamagana District in Rwanda. The R coefficient of 0.820 reveals that crop intensification project activities has a positive relationship on the health improvement. The coefficient of determination .672 R square also indicates that crop intensification project activities explain 67.2 % the variability of progressing in improved health status. Therefore, this shows that predictors of crop intensification project activities such as increased land of cultivation, improved seeds and yields affect the progress of improved health by 67.2% in CIP Munyaga Sector of Rwamagana District in Rwanda. Therefore, referring on the findings of the work the researcher is recommending local authorities to encourage farmers to join associations for crop intensification in order to enhance their livelihoods, to provide efficient management of the peasant masses to make possible means easier for maize farmers to access the most modern maize growing equipment, educate farmers in fertilizer use and integrated soil fertility and crop management and maintain an enabling market environment that encourage private sector investments. The researcher would like to recommend to improve access of information on market, price, supply availability, provide information to investors related to crop profitability, accessibility to finance, and to have considerable collaboration with sector and district agronomists in order to achieve production target. In conclusion, the findings have revealed that the livelihood of maize farmers has improved after joining crop intensification because the same results have proved a positive and significant relation between crop intensification project activities and livelihood improvement in Munyaga Sector, Rwamanaga District of Rwanda.